The Role of Teachers' Professional Development in Assessing Students' Competencies in the Foreign Language Curriculum - Roseni, Emilda; Haxhihyseni, Shqipe (Journal of Education Culture and Society, 2025)
Aim. This article aims to examine the professional development of foreign language teachers concerning the assessment of students' competencies during the implementation of the curriculum. The study posits that effective assessment is a crucial tool for evaluating student competencies in foreign languages and guiding instructional practices.Method. A quantitative study was conducted using questionnaires distributed to 250 foreign language teachers in Albania from 9-year and high schools in the cities of Tirana, Elbasan, and Durrës in Albania were selected during the school year 2024-2025. This research analysed the impact of teachers' experience and understanding of assessment tools on student achievement, while also considering differences in assessment practices between rural and urban schools.Results. The findings indicate varied levels of understanding among teachers regarding assessment tools, as well as significant differences in the assessment of student competencies based on geographical context.Conclusion. The paper concludes that a holistic approach to assessment is necessary to support continuous improvement, foster learner autonomy, and ensure equitable learning opportunities. This approach is essential for enhancing the effectiveness of foreign language education and achieving curriculum objectives.Research Restrictions. The study was limited to three major urban centers in Albania and may not fully reflect the diversity of practices across other regions or private educational institutions.Cognitive Value. This research contributes to the understanding of how assessment practices shape the effectiveness of language instruction and supports the design of targeted professional development initiatives aimed at improving educational equity and outcomes in foreign language learning.